Visual perception and recollection of pictures in packaging design - Nikolaus, Ulrich; Bendlin, Sandra (Journal of Print and Media Technology Research, 2023)
Continuing an ongoing study to analyze consumer reactions to packaging design, eye tracking test results that explore the visual perception and recollection of pictures in packaging design are presented. Particularly, the extent and reliability of human recollection of pictorial elements on packages that were seen only for a short period of time is discussed in detail. These results help to better understand the visual impact which pictures in packaging design have on consumers. The results suggest that consumers discern a great deal of graphical detail in pictures within a very short period of time, but that this recollection varies among users and is sometimes inaccurate. Furthermore, it could be shown that viewers in general describe coherent (albeit sometimes inaccurate) interpretations of visual stimuli instead of isolated details of visual design.